Effect of marketing mix, firm generated content, and celebrity endorsement towards customer’s purchase decision in choosing dental hospitals during covid – 19 pandemic - Agnella Gwenisa; Rudy Pramono (Enrichment : Journal of Management, 2022)
There were many dental clinics and dental hospitals that experienced a decline in sales and were also changes in people’s behaviour in purchasing decision during the Covid – 19 pandemic. People tend to be more careful and thorough in making decisions in spending. Dental hospitals must still survive, hence dental hospitals can implement marketing mix (product, price, promotion), firm generated content, and celebrity endorsement to attract patients. This study aims to determine how celebrity endorsement, company-generated content, and the marketing mix influence customer purchase decisions during the COVID-19 pandemic. Purposive non-probability sampling was used in this quantitative study, which was conducted on a sample of 100 patients from Trisakti University Dental Hospital. A questionnaire is used to collect the data, which is then analyzed using descriptive and inferential data analysis. In contrast to price, promotion, and celebrity endorsement, it can be concluded that customer purchase decisions regarding dental hospitals are significantly and positively influenced by product and firm generated content. Trisakti University Dental Hospital should do further research in a different time frame and a larger population size. Keywords: Marketing Mix, Firm Generated Content, Celebrity Endorsement, Covid - 19